#### Answer

{($\frac{18}{7}$,$\frac{8}{7}$)}

#### Work Step by Step

2x-y=4
2x-2x-y=4-2x
-y=4-2x
-1(-y)=-1(4-2x)
y=-4+2x
Plug this value for y into the other equation.
3x-5(-4+2x)=2
3x-5(-4)-5(2x)=2
3x+20-10x=2
3x-10x+20=2
-7x+20=2
-7x+20-20=2-20
-7x=-18
x=$\frac{-18}{-7}$
x=$\frac{18}{7}$
Plug this value for x into the first equation to solve for y.
y=-4+2($\frac{18}{7}$)
y=-4+$\frac{36}{7}$
y=-$\frac{28}{7}$+$\frac{36}{7}$
y=$\frac{8}{7}$
Therefore the solution is {($\frac{18}{7}$,$\frac{8}{7}$)}